Epistemologi Empirisme - M, Marilang; Haq, Fitri Maylan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to explain the epistemology of empiricism and the figures who support this school. To obtain relevant research results, this research uses data collection techniques or literature studies. The results of this research are that epistemology examines what science really is, where the source of knowledge comes from, and how the process occurs. Epistemology requires scientific methods in obtaining knowledge, one of these methods is empiricism, which emerged as a reaction to the weaknesses of rationalism. Empiricism is a doctrine where the source of knowledge must be sought in experience or the sensory. The supporting figures for this flow are: